Balancing Work and Caregiving: A Guide for Employers - Martie Gillen; Carolyn S. Wilken (EDIS)
Over 4 million people in Florida care for older family members or friends, and these people often must balance work and home responsibilities. Employers need to be aware of how to support their employees who are also caregivers. This could include support programs for caregivers, flexible schedules, or other work accommodations. This revised 3-page fact sheet was written by Martie Gillen and Carolyn S. Wilken, and published by the UF Department of Family, Youth, and Community Sciences, August 2012.